Evaluasi Pentingnya Lokasi Sentra Oleh-Oleh untuk Pariwisata Kota Batam - Nofriani Fajrah; Sri Zetli (Prosiding, 2020)
Batam City is now starting to turn into a tourism city. However, Batam tourism has not been equipped with a souvenir sales center to introduce Batam city characteristics. The aims of this research is to evaluate the important of availability the souvenir centre for Batam City Tourism. The method used is the descriptive-quanititative model from the data that has been collected. The data collected by voice of curtomer method to find the gap of the needed of souvenir centre for the tourist. Based on the research results will find that the location of souvenir centre is important to support Batam Tourism. This is because souvenirs are part of the process of introducing the culture of an area to tourists. Therefore, the Batam city government needs to pay attention to the needs of tourists who travel to Batam City by providing a souvenir center in the tourist center of Batam City.